Clinical and Ultrasound Biomicroscopic Characteristics of Congenital Fibrovascular Pupillary Membrane-Induced Secondary Glaucoma - Zhu, Yingting; Fang, Lei; Zhong, Yimin; Oatts, Julius; Han, Ying; Lin, Shufen; Chen, Liming; Zhou, Xiaodi; Su, Yihua; Liu, Pingping; Liu, Xing (Frontiers in Medicine, 2021)
Purpose: The purpose of this study was to describe and summarize the clinical features of congenital fibrovascular pupillary membrane induced secondary glaucoma (CFPMSG). Design: Cross-sectional case series. Methods: Eyes of 32 patients with CFPMSG were enrolled. Demographic data including gender, laterality, age at presentation, and age at onset of glaucoma were collected. Patients underwent comprehensive ophthalmic examinations and ultrasound biomicroscopy (UBM). CFPMSG eyes were classified into 3 groups based on UBM findings and intergroup analysis was performed using analysis of variance (ANOVA). Results: The average age at presentation was 2.4 ± 4.6 months (mean±standard deviation) and at glaucoma onset was 3.8 ± 4.5 months. Compared to normal fellow eyes, all affected eyes had increased intraocular pressure (IOP), axial length, corneal diameter, and central corneal thickness, and decreased ACD (all P≤0.001). Twenty-two affected eyes (68.8%) had evidence of glaucomatous optic neuropathy. Based on iris configuration on UBM, eyes were classified as 53% type I (“U” shape), 34% type II (“Y” shape), and 13% type III (no anterior chamber). IOP in type II (33.8±5.9mmHg) and III (35.2±5.9mmHg) was significantly higher than in type I eyes (26.5±5.1mmHg). The ACD was shallower in type II compared to type I (P=0.045). Conclusion: CFPMSG is characterized by ocular hypertension, corneal enlargement and edema, axial length elongation, and glaucomatous optic neuropathy. Glaucoma in this condition is secondary to pupillary block and angle closure. UBM provides important information for the diagnosis and classification of CFPMSG. This novel classification system demonstrated varying levels of severity and may guide on management of this disease.